Peculiarities of legal regulation of state procurement contract (Journal of actual problems of jurisprudence, 2019)
The article is devoted to the problems of the legal nature and legal regulation of the state procurement contract, as well as it gives a legal assessment. There is also considered the relations of parties after the recognition of the contract as null.The relevance of the research topic is determined by several factors based on the need to study issues of scientific-theoretical, legislative nature.The state procurement contract, along with domestic legislation, is regulated by the laws of Russia, America, Germany, France, Switzerland and other countries. The importance of this study is growing due to the fact that state participates as a party to meet its needs, which results in the expenditure of funds from the state budget. In addition, in domestic science there is no comprehensive theoretical study of this topic from a legal point of view. This work aims to determine the conditions, the consequences of the recognition of the contractvoid. There were used general scientific, historical and comparative analysis methods in the research.The legal analysis carried out by the authors makes it possible to provide recommendations on howto improve the national legal regulation of these problems.Key words: customer, state procurement contract, state order, performer.